Mechanical Ventilation and Diaphragmatic Atrophy in Critically Ill Patients: An Ultrasound Study. Issue 7 (July 2016) - Zambon, Massimo; Beccaria, Paolo; Matsuno, Jun; Gemma, Marco; Frati, Elena; Colombo, Sergio; Cabrini, Luca; Landoni, Giovanni; Zangrillo, Alberto
Abstract : Objective: Mechanical ventilation contributes to diaphragmatic atrophy and dysfunction, and few techniques exist to assess diaphragmatic function: the purpose of this study was to quantify diaphragm atrophy in a population of critically ill mechanically ventilated patients with ultrasound and to identify risk factors that can worsen diaphragmatic activity. Design: Prospective observational study. Setting: ICU of a 1, 200-bed university hospital. Patients: Newly intubated adult critically ill patients. Interventions: Diaphragm thickness in the zone of apposition was measured daily with ultrasound, from the first day of mechanical ventilation till discharge to the main ward. Measurements and Main Results: Daily atrophy rate (ΔTdi/d) was calculated as the reduction in percentage from the previous measurement. To analyze the difference in atrophy rate (ΔTdi/d), ventilation was categorized into four classes: spontaneous breathing or continuous positive airway pressure; pressure support ventilation 5–12 cm H2 O (low pressure support ventilation); pressure support ventilation greater than 12 cm H2 O (high pressure support ventilation); and controlled mechanical ventilation. Multivariate analysis with ventilation support and other clinical variables was performed to identify risk factors for atrophy. Forty patients underwent a total of 153 ultrasonographic evaluations. Mean (SD) ΔTdi/d was –7.5% (12.3) during controlled mechanical ventilation, –5.3% (12.9) at high pressure support ventilation, –1.5% (10.9) at low pressure support ventilation, +2.3% (9.5) during spontaneous breathing or continuous positive airway pressure. At multivariate analysis, only the ventilation support was predictive of diaphragm atrophy rate. Pressure support predicted diaphragm thickness with coefficient –0.006 (95% CI, –0.010 to –0.002; p = 0.006). Conclusions: In critically ill mechanically ventilated patients, there is a linear relationship between ventilator support and diaphragmatic atrophy rate.